HIV Infection Is an Independent Predictor of Mortality Among Adults with Reduced Level of Consciousness in Uganda - Mbonde, Amir A.; Mbatidde, Lydia; Demaerschalk, Bart M.; Aden, Abdirahim A.; Zhang, Nan; Butterfield, Richard; Muhindo, Rose; Kayanja, Adrian; O’Carroll, Cumara B. (The American journal of tropical medicine and hygiene, 2022)
The clinical epidemiology of adults admitted with reduced level of consciousness (LOC) in sub-Saharan Africa (SSA) and the impact of HIV infection on the risk of mortality in this population is unknown. We secondarily analyzed data from a cohort study that enrolled 359 consecutive adults with reduced LOC presenting to Mbarara Regional Hospital in Uganda with the aim of comparing the prognostic utility of the Full Outline of Unresponsiveness (FOUR) score to the Glasgow Coma Scale (GCS) Score. For this analysis, we included 336 individuals with known HIV serostatus, obtaining clinical, laboratory, and follow-up data. We recorded investigations and treatments deemed critical by clinicians for patient care but were unavailable. We computed mortality rates and used logistic regression to determine predictors of 30-day mortality. The median GCS was 10. Persons living with HIV infection (PLWH) accounted for 97 of 336 (29%) of the cohort. The 30-day mortality rate in the total cohort was 148 of 329 (45%), and this was significantly higher in PLWH (57% versus 40%, adjusted odds ratio [aOR] 2.39: 95% confidence interval [CI]: 1.31–4.35, P50.0046). Other predictors of mortality were presence of any unmet clinical need (aOR 1.72; 95% CIL 1.04–2.84, P50.0346), anemia (aOR 1.68; 95% CI: 1.01–2.81, P50.047), and admission FOUR score,12 [aOR 4.26; 95% CI: 2.36–7.7, P < 0.0001). Presentation with reduced LOC in Uganda is associated with high mortality rates, with worse outcomes in PLWH. Improvement of existing acute care services is likely to improve outcomes.
Keywords: HIV Infection; Mortality; Consciousness; Population; Uganda